Paucity of high‐quality studies reporting on salt and health outcomes from the science of salt: A regularly updated systematic review of salt and health outcomes (April 2017 to March 2018). Issue 2 (27th December 2018) - Petersen, Kristina S.; Rae, Sarah; Venos, Erik; Malta, Daniela; Trieu, Kathy; Santos, Joseph Alvin; Thout, Sudhir Raj; Webster, Jacqui; Campbell, Norm R. C.; Arcand, JoAnne
Abstract: The purpose of this review is to identify, summarize, and critically appraise studies on dietary salt and health outcomes that were published from April 2017 to March 2018. The search strategy was adapted from a previous systematic review on dietary salt and health. Identified studies were screened based on a priori defined criteria to identify publications eligible for detailed critical appraisals. Overall, 6747 citations were identified by the search strategy, and 42 health outcome studies were identified. Three of the 42 studies met the criteria for methodological quality and health outcomes and underwent detailed critical appraisals and commentary. In addition, a systematic review and meta‐analysis was critically appraised, although it did not strictly meet our methodological criteria. All four of the studies critically appraised found that sodium reduction improved blood pressure, especially in individuals with hypertension. In addition, sodium reduction reduced albuminuria in patients with stage 1‐3 chronic kidney disease. Examination of the time course of blood pressure responses to sodium reduction revealed lowering sodium in the context of an average American diet may not produce maximal blood pressure reductions within a 4‐week intervention period. This review provides further evidence of the benefit of sodium reduction for blood pressure lowering and gives insights into the subgroups of the population that may derive the greatest benefit from sodium reduction and the time course required to see benefit. Only three high‐quality studies were identified during this 12‐month review period, highlighting the critical need for more well‐conducted rigorous studies in this area.